STRENGTHENING LOCAL WISDOM VALUES THROUGH P5 ACTIVITIES AT SD NEGERI HINDU 1 BONA - Ketut Manik Asta Jaya; I Wayan Lali Yogantara (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2025)
This research aims to explore the efforts to strengthen local wisdom through the Project to Strengthen the Profile of Pancasila Students (P5) at SD Negeri Hindu 1 Bona. The study employs a qualitative method with a descriptive approach. The research sample consists of 10 fifth- and sixth-grade students from SD Negeri Hindu 1 Bona and 5 teachers. The results indicate that the process of strengthening local wisdom through P5 activities begins with a diagnostic assessment of the students, followed by determining activities based on local wisdom themes, such as dharmagita, dance, and the creation of various religious ceremony tools. The implementation of P5 starts with the contextualization phase, which includes discussions of various information related to the project activities, followed by the action phase, which is conducted two to three times. The process is then continued with a reflection phase and follow-up. The conclusion is that P5 activities at SD Negeri Hindu 1 Bona are crucial for reinforcing the values of local wisdom, especially through activities integrated with Balinese culture. Each project is designed to develop students' potential while fostering a love for local culture.